Design, synthesis and evaluation of MRI ligands for in vivo imaging of protease activity - Krupa, James L. (2016)
This thesis details the design and synthesis of a small library of 19F MRI MMP probes containing an MMP substrate bound to a paramagnetic agent (gadolinium contrast agent) with a fluorine containing group at the opposite terminus. The largest obstacle in the synthesis of the probe was the conjugation of the paramagnetic agent. Multiple different modifications to the GdIII chelators AAZTA (6-amino-6-methylperhydro-1,4-diazepinetetraacetic acid) and DOTA (1,4,7,10-tetraazacyclododecane-1,4,7,10-tetraacetic acid) are detailed, as well as methods for the conjugation.